REDUKSI PH, BOD DAN COD DALAM GREY WATER DENGAN PROSES ELEKTROKUAGULASI-SEDIMENTASI - Monik Kasman; Siti Umi Kalsum; Asep Suma Aditia (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Grey water is classified as domestic wastewater generated from residences drain, public and comercial facilites. In this research, grey water sample was obtained from residence at Jl. Kasturi I RT. 01 No. 32 Kelurahan Beliung Kecamatan Kota Baru Jambi. This research was aimed to observe the capability and the effectivity of combined process of electro-coagulation-sedimentation in reducing pH,  BOD (Biological Oxygen Demand) and COD (Chemical Oxygen Demand) contained  in grey water. Final effluent concentration was compared with The Indonesian Act of  no. 82/2001 concerning on management  of water quality and water pollution control. According to the results, reducing of pH, BOD and COD within voltage of 40 volt and detention time of  30 minutes, 60 minutes and 90 minutes in electro-coagulation-sedimentation  reactor were respectively 19,81 %,  48,41 %, dan 25,71 %. Excluding pH, final effluent concentration was still below concentration of parameter standardized in The Indonesian Act of no. 82/2001 concerning on management  of water quality and water pollution control.Key words : grey water, electrocoagulation-sedimentation, pH, BOD, and COD